2019
DOI: 10.1111/nep.13474
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and acceptability of treatment to eradicate nasal Staphylococcus aureus carriage among haemodialysis patients

Abstract: S. aureus decolonisation using topical or systemic treatments was successful for many haemodialysis patients, and provided a month free of S. aureus colonisation. Although decolonisation treatment provided a shorter duration of success for persistent carriers in comparison with intermittent carriers, persistent carriers are likely to gain the most from effective decolonisation strategies. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…There have been implementations of S. aureus decolonisation in haemodialysis clients. A New Zealand based study [48] targeted both MSSA and MRSA and showed that decolonisation persists for some weeks. This study did not address the burden of infection.…”
Section: Discussionmentioning
confidence: 99%
“…There have been implementations of S. aureus decolonisation in haemodialysis clients. A New Zealand based study [48] targeted both MSSA and MRSA and showed that decolonisation persists for some weeks. This study did not address the burden of infection.…”
Section: Discussionmentioning
confidence: 99%